Kindlin-2 Modulates the Survival, Differentiation, and Migration of Induced Pluripotent Cell-Derived Mesenchymal Stromal Cells - Mohsen Moslem; Reto Eggenschwiler; Christian Wichmann; Raymund Buhmann; Tobias Cantz; Reinhard Henschler (Stem Cells International)
Kindlin-2 is a multidomain intracellular protein that can be recruited to β-integrin domains to activate signaling, initiate transcriptional programs, and bind to E-cadherin. To explore its involvement in cell fate decisions in mesenchymal cells, we studied the effects of Kindlin-2 modification (overexpression/knockdown) in induced pluripotent cell-derived mesenchymal stromal cells (iPSC-MSCs). Kindlin-2 overexpression resulted in increased proliferation and reduced apoptosis of iPSC-MSCs, as well as inhibition of their differentiation towards osteocytes, adipocytes, and chondrocytes. In contrast, siRNA-mediated Kindlin-2 knockdown induced increased apoptosis and increased differentiation response in iPSC-MSCs. The ability of iPSC-MSCs to adhere to VCAM-1/SDF-1α under shear stress and to migrate in a wound scratch assay was significantly increased after Kindlin-2 overexpression. In contrast, inhibition of mixed lymphocyte reaction (MLR) was generally independent of Kindlin-2 modulation in iPSC-MSCs, except for decreased production of interleukin-2 (IL-2) after Kindlin-2 overexpression in iPS-MSCs. Thus, Kindlin-2 upregulates survival, proliferation, stemness, and migration potential in iPSC-MSCs and may therefore be beneficial in optimizing performance of iPSC-MSC in therapies.